Amyotrophic Lateral Sclerosis - Araki, Toshiyuki (Exon Publications, 2021)
Amyotrophic lateral sclerosis is a fatal, progressive neurodegenerative disorder characterized by motor neuron cell death in the brain and spinal cord. The typical disease symptom is the rapid loss of muscle control, which eventually leads to the complete paralysis of voluntary muscles of the entire body. There is no curative treatment for amyotrophic lateral sclerosis. The rarity of the disease and the difficulties in accurate early diagnosis are the major challenges in the proper understanding of the disease and the development of curative therapy. This book brings together a team of experts, both clinicians and basic scientists, to provide a comprehensive understanding of amyotrophic lateral sclerosis, challenges, and approaches to combat this devastating disease. The clinical chapters provide excellent views of diagnosis, pathology, management, and the problem of diagnostic delay. The basic science chapters provide a comprehensive description of pathomechanisms and therapies with emphasis on dysfunctional astrocytes, impaired synaptic transmission, defective axonal transport, biomarkers, cell-based therapies, and gut microbiota. The book is primarily aimed at clinicians and basic scientists; however, it will likely be of interest to a wide audience interested in amyotrophic lateral sclerosis.